Prominent Mistakes of Endowment Surveillants & Those of Similar and Methods Treatment - Al-Luhidan, Mohammad Abdulaziz (Journal of Islamic Sciences, 2022)
The study aimed at identifying the mistakes of the endowment Surveillant from the legal, regulatory and administrative aspects, as well as determining the causes of these errors and developing the necessary solutions and treatments. The study adopted the descriptive survey method, which depends on the study of the phenomenon as it is in reality, and it was clarified quantitatively and studied qualitatively. In addition to the commentary and marginalization approach in attributing Quranic verses to their places, as well as hadiths and effects from the books of the Sunnah, quoting texts from their sources, and linguistic definition of terms. The study dealt with the definition of the endowment, its pillars, legitimacy and provisions, the definition of the endowment overseer and its provisions and conditions, as well as defining the terms of the beholder and the limits of his mandate and powers and his functions, tasks and responsibilities. study also included identifying those errors, their causes and the results of their practice. The study came out with the development of mechanisms to deal with these errors, the most important of which is the accountability and the activation of control of all kinds, and the application of governance principles to control the workflow within the endowment institutions. And confronting the deviations that hinder the achievement of the goals of the endowment institutions, in addition to being a means to achieve the principle of control and performance evaluation and contribute to identifying individual performance defects, determine the level of efficiency in achieving goals, protect from falling into mistakes, and enhances a sense of vigilance from falling into neglect or dishonesty.